Thor : the mighty avenger. Vol. 1 - Langridge, Roger (Marvel Comics, 2010)
Banished from his home, stripped of his power, Thor arrives on this world with a chip on his shoulder and ready for a fight! Fortunately, the villainous Mr. Hyde awaits!